2016
DOI: 10.1021/acs.est.5b04145
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ferric Salt and Cactus Mucilage for Arsenic Removal from Water

Abstract: New methods to remediate arsenic-contaminated water continue to be studied, particularly to fill the need for accessible methods that can significantly impact developing communities. A combination of cactus mucilage and ferric (Fe(III)) salt was investigated as a flocculation-coagulation system to remove arsenic (As) from water. As(V) solutions, ferric nitrate, and mucilage suspensions were mixed and left to stand for various periods of time. Visual and SEM observations confirmed the flocculation action of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…The literature on arsenic removal by coagulation-flocculation with chitosan is sparsely reported [27,33,34,35,36,37,38,39,40]. In general, typical examples of coagulation-flocculation studies have focused on inorganic arsenic species, either arsenate (As(V); HAsO 4 2− ) and/or arsenite (As(III); H 3 AsO 3 ) species [27].…”
Section: Application Of Chitosan In Coagulation-flocculation For Wmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on arsenic removal by coagulation-flocculation with chitosan is sparsely reported [27,33,34,35,36,37,38,39,40]. In general, typical examples of coagulation-flocculation studies have focused on inorganic arsenic species, either arsenate (As(V); HAsO 4 2− ) and/or arsenite (As(III); H 3 AsO 3 ) species [27].…”
Section: Application Of Chitosan In Coagulation-flocculation For Wmentioning
confidence: 99%
“…This is advantageous since increased levels of Fe(III) in water are less aesthetically pleasing in taste and smell [39]. Baskan et al [35] used the Box–Behnken design to study optimal parameters for the coagulation of arsenate.…”
Section: Application Of Chitosan In Coagulation-flocculation For Wmentioning
confidence: 99%
“…38 For instance, when mucilage was added in combination with iron, >90% removal of As was attained in just 10 min. 61 When mucilage was added as a pure powder or in membrane form, up to 50% As or 18-20% As was removed, respectively. 55 , 57 Sibaja et al, 62 Vollrath et al, 14 and Truss 9 have also used natural fi bers in functional applications such as textiles and tissue scaffolds.…”
Section: Sylvia W Thomas and Norma A Alcantar Guest Editorsmentioning
confidence: 99%
“…Recently, its role as a natural occulant for arsenic removal has been reported. 24 Li et al reported the excellent lubrication properties of mucilage that result from the hydration layer between the polymer nanosheets in mucilage. 25 Mucilage was used as food thickener, food emulsier, and adhesive for lime and plasticizer.…”
Section: Introductionmentioning
confidence: 99%